Effect of dietary soy lecithin on laying performance, egg quality and meat texture of aged layer hen - Akit, Henny; Sazili, Awis Qurni; Ismail, Nurul Afifah; Atan, Nur Atiqah; Shazali, Nurhazirah; Loh, Teck Chwen (Universiti Putra Malaysia Press, 2016)
This study was conducted to determine the laying performance, egg quality and meat texture of aged layer hens fed with soy lecithin. A total of 100 layer hens (Novogen Brown), aged 76-weeks old, were randomly assigned to five treatment groups and treated as follows: basal diet with 0% (control), 2%, 4%, 6% and 8% soy lecithin, respectively. After four weeks of treatment, lecithin showed no improvement in body weight gain, egg mass, egg production, feed intake, feed conversion efficiency, egg quality and meat texture. Meanwhile, egg weight increased in birds fed with 2% lecithin (P=0.02) and this might be attributed to the high linoleic acid content in soy lecithin. The results implied that feeding hens with 2% lecithin increased egg weight but it had no beneficial effects on other laying performance parameters. Thus, it is of interest to investigate potential benefits of lecithin on different dietary fat sources.